Efisiensi Teknis Usahatani Padi Organik Di Provinsi Lampung - Sri Puji Lestari; Sri Handayani; Eka Aryani; Maria Kristina (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
A healthy lifestyle is related to food consumption patterns, namely consuming organic food. One of the most commonly consumed organic food commodities is organic rice. Organic food products are cultivated without the use of chemicals. Changes in people's consumption patterns have led to an increase in demand for organic rice. However, at present, the productivity of organic rice farming is still low when compared to the productivity of conventional rice farming. The low productivity is thought to be caused by the inefficient allocation of production factors. This study aims to analyze the factors that affect organic rice production, examine whether organic rice farming in Lampung Province has been technically efficient, and find out what factors cause technical inefficiency in organic rice farming in Lampung Province. The location of this research is Beringin Kencana Village, Candipuro District, South Lampung Regency, and Purwokencono Village, Sekampung Udik District, East Lampung Regency in July-August 2022. Sampling was carried out by census. The research method used is the Stochastic Frontier Cobb-Douglas production function. The results showed that the factors that affect the production of organic rice are land area, the number of seeds, and the use of organic pesticides. The average level of technical efficiency is 0.91. Factors that affect technical inefficiency are the age of the farmer, farming experience, and participation in extension.